Apartmentalization and middle classness: urban socio-spatial change in the period 1950s-1970s - Duru, Aslı. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
The Turkish experience of the housing issue makes possible the display of remarkable ways, interrelations between individuals and their residential practices as well as the functional necessities developed within the context of republican modernism. During the rapid urbanization era in Turkey the home as concept and physical unit has been transformed in accordance with the changing social and physical norms and values of living. This study aims to explore the specific material and social ways, apartment home as subjective experience in the period 1950s and the 1970s provided the domain for the urban population to experience change in their subjective capacities and become middle class. The main issue the study questions is whether and to what extent the spatial chaos the processes of unplanned/spontaneous urbanization and residential change have caused in the physical environment, has its counterpart in the minds of dwellers in their becoming middle class.
Keywords: Urbanization -- Turkey.; Cities and towns -- Turkey -- Istanbul -- Growth.